Nasopharyngeal carcinoma—some closing remarks - Wee, Joseph Tien Seng; Soong, Yoke-Lim; Poh, Sharon Shuxian; Chua, Melvin Lee Kiang (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
We thought it would be appropriate for us as editors to close this issue with some personal reflections on certain areas with respect to nasopharyngeal carcinoma (NPC).